1999
DOI: 10.1139/g98-154
|View full text |Cite
|
Sign up to set email alerts
|

Genome structure and evolution in the allohexaploid weed Avena fatua L. (Poaceae)

Abstract: Allohexaploid wild oat, Avena fatua L. (Poaceae; 2n = 6x = 42), is one of the world's worst weeds, yet unlike some of the other Avena hexaploids, its genomic structure has been relatively little researched. Consequently, in situ hybridisation was carried out on one accession of A. fatua using an 18S-25S ribosomal DNA (rDNA) sequence and genomic DNA from A. strigosa (AA-genome diploid) and A. clauda (CC-genome diploid) as probes. Comparing these results with those for other hexaploids studied previously: (i) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 21 publications
1
16
1
Order By: Relevance
“…We observed that the terminal A/D translocations in A. fatua occurred on the 1C and 7C. Yang et al (1999) reported that the terminal A/D-C translocations on the 1C, 3C or 4C, and in addition, detected a terminal A/D translocation on each arm of chromosome 7C. In our study, a terminal A/D translocations in A. sterilis was observed on chromosomes 1C and 7C and corresponded to the results of Jellen et al (1994).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…We observed that the terminal A/D translocations in A. fatua occurred on the 1C and 7C. Yang et al (1999) reported that the terminal A/D-C translocations on the 1C, 3C or 4C, and in addition, detected a terminal A/D translocation on each arm of chromosome 7C. In our study, a terminal A/D translocations in A. sterilis was observed on chromosomes 1C and 7C and corresponded to the results of Jellen et al (1994).…”
Section: Discussionsupporting
confidence: 86%
“…Although both tetraploid species, A. maroccana and A. murphyi were detected the translocation segment on medium length chromosome of seven pairs of C-genome chromosomes, two hexaploid species, A. byzantina (our result) and A. fatua (Yang et al, 1999) were also detected on medium length chromosome. It suggests that the chromosomes with the segment of two hexaploids are conservative.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Chromosome characterization and genome identification have advanced significantly with the development of molecular cytogenetics through fluorescence in situ hybridization (FISH) and genomic in situ hybridization (GISH) techniques (Capdeville et al, 2008;Fukui, 2005;Hwang et al, 2010Hwang et al, , 2012Levsky and Singer, 2003;Park et al, 2010). Indeed, these methods have been used to investigate genome structure and inter-genomic relationship of hybrid plants (Jellen et al, 1994;Kenton et al, 1993), allopolyploid species (Cao, 2003;Devi et al, 2005;Yang et al, 1999), and recombinant breeding lines (Hwang et al, 2012;Lou et al, 2010;Vasconcelos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%